Mejora en la prevención de riesgos laborales en seguridad y salud ocupacional: caso empresa metalmecánica en una unidad minera - Olazábal Ticona, Evelyn Lisbeth (2025)
The mine currently under study is located in Peru and works with contractors to execute related activities. The employer must promote a culture of occupational risk prevention during activities. In this research article, the agile methodology was used to identify its processes and the performance status in each guideline of the Occupational Health and Safety Management System (OHSMS). This was the basis for the design and implementation of tools to manage the measurement and control of the OHSMS. The results demonstrated that the measurement and timely control of the OHSMS increased occupational risk prevention compliance from 62% to 89%, which made it possible to safely complete the project.